The Role of Student Self-Government in Ensuring the Quality of Higher Education - Oksana Kondur; Nataliia Koturbash; Galyna Mykhaylyshyn (Vasyl Stefanyk Precarpathian National University, 2021)
The current state of development of the Ukrainian state requires further reform of all spheres of life of the Ukrainian community. The democratization of the principles of higher education needs special attention. Since students are the driving force of society, the developer of unique ideas of the present and future, a factor in the formation and development of civil society, so the democratization of student life, active participation of students in different organizations, leadership skills and teamwork, making the right decisions and responsibility for their implementation becomes especially relevant during educational transformations. Student governments have a significant impact on youth. The range of such influence primarily extends to the realization of the student in the modern world, meeting his/her needs, both in education and in other areas, including volunteer, artistic, managerial, social and more. Therefore, membership in student organizations gives a young person a valuable life experience, which can later be implemented in practice. Participation in student self-government contributes to the development of students' leadership qualities, the formation of their active civic life positions. That is, the activities of student government in higher education institutions are aimed at forming the values of the younger generation. At the same time, student self-government is a unique factor in reforming the modern system of the educational process in higher education institutions. Applicants are actively involved in the development, implementation, and accreditation of educational programs, are experts in the accreditation of the National Agency for Quality Assurance in Education. The article demonstrates the effectiveness of student self-government bodies in higher education institutions on specific examples, substantiates the need for their development as one of the factors that contributes to the improvement of quality assurance processes in education.